2019
DOI: 10.1097/j.pain.0000000000001546
|View full text |Cite
|
Sign up to set email alerts
|

Can a brief psychological expectancy intervention improve postoperative pain? A randomized, controlled trial in patients with breast cancer

Abstract: Pain after surgery remains a major health problem, calling for optimized treatment regimens to maximize the efficacy of pharmacological interventions. In this randomized controlled trial, we tested in a routine surgical treatment setting whether postoperative pain can be reduced by a brief preoperative intervention, ie, positive verbal suggestions in combination with sham acupuncture, designed to optimize treatment expectations. We hypothesized that the expectancy intervention as add-on to patient-controlled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 50 publications
0
12
1
3
Order By: Relevance
“…Benson et al. [ 3 ] konnten bei Patientinnen, die einer brusterhaltenden Operation unterzogen wurden, ergänzend zur Opioidanalgesie mithilfe einer kurzen psychologischen Erwartungsintervention postoperative Schmerzen reduzieren. Sie verglichen den Einfluss positiver Suggestionen mit neutralen Suggestionen und untersuchten zusätzlich den Einfluss von Sham-Akupunktur.…”
Section: Interventionen Zur Beeinflussung Von Behandlungserwartungen ...unclassified
“…Benson et al. [ 3 ] konnten bei Patientinnen, die einer brusterhaltenden Operation unterzogen wurden, ergänzend zur Opioidanalgesie mithilfe einer kurzen psychologischen Erwartungsintervention postoperative Schmerzen reduzieren. Sie verglichen den Einfluss positiver Suggestionen mit neutralen Suggestionen und untersuchten zusätzlich den Einfluss von Sham-Akupunktur.…”
Section: Interventionen Zur Beeinflussung Von Behandlungserwartungen ...unclassified
“…Our findings suggest that emotional states predict treatment expectations and, therefore, play a critical role in the treatment outcome for postoperative pain. According to the literature concerning placebo mechanisms, positive treatment expectations are crucial to enhance surgical treatment outcomes ( 44 , 45 ). However, underlying mechanisms have to be uncovered to be able to influence treatment expectations.…”
Section: Discussionmentioning
confidence: 99%
“…Pain was significantly lower in the patients receiving positive suggestions, regardless of whether they also received sham acupuncture. The researchers concluded that these results suggest a benefit of psychological strategies targeting positive expectations for improving pain, although they likely are most effective when used in combination with other established elements of physician‐patient communication (e.g., enhanced empathy, trust, caring attitude) 9 …”
Section: Psychological Interventionmentioning
confidence: 99%